University Professor Training in Times of COVID-19: Analysis of Training Programs and Perception of Impact on Teaching Practices - Anabel Ramos-Pla (MDPI AG, 2021)
During the confinement and post-confinement period, the continuous training centers at different Catalan universities adapted the lifelong learning of professors. The present study analyzes the education of lecturers from Catalan universities before and after the pandemic, as well as their perception of its impact. A documentary analysis was performed of the continuous training programs for professors. Posteriorly, an enquiry was made about the perception of impact of this training, through a descriptive and inferential analysis with the use of a questionnaire designed ad hoc. Results indicated an increase in training associated with institutional digital tools, online evaluation, and design of online courses. The efforts by the professors to implement the knowledge acquired is underlined, with a higher perception of impact observed in the areas of Social and Legal Sciences and Arts and Humanities. In addition, the main difficulties perceived were the lack of time for adapting their practice of teaching with the knowledge acquired, as well as the complexity of performing an online evaluation. It is concluded that there is a need for continuous training programs that help establish support networks and collaboration between professors for the improvement of teaching, and in which one of the priorities is online evaluation.